Canadian International Petroleum Conference 2003
DOI: 10.2118/2003-067
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Formation Damage Characteristics of Xanthan Gum Solutions Used for Drilling, Drill-In, Spacer Fluids, and Coiled Tubing Applications

Abstract: Xanthan Gum has been used extensively as a viscosifier in the oil industry for different applications due to its unique rheological properties. An experimental study has been conducted to investigate the formation damage characteristics of Xanthan Gum based fluids and the results are presented in this paper.A series of core flow experiments have been conducted to investigate the possible relationship among the Xanthan Gum concentration, fluid extensional viscosity, shear viscosity, filtration loss characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…Results of similar analyses conducted by using Xanthan Gum solutions were presented earlier 5 . A comparison of the results of PHPA tests with the ones from Xanthan Gum tests 5 are also provided in this paper.…”
Section: Extensional Viscositysupporting
confidence: 55%
See 3 more Smart Citations
“…Results of similar analyses conducted by using Xanthan Gum solutions were presented earlier 5 . A comparison of the results of PHPA tests with the ones from Xanthan Gum tests 5 are also provided in this paper.…”
Section: Extensional Viscositysupporting
confidence: 55%
“…The flow tests were conducted by injecting PHPA (this study) and XG (Khan et al 5 ) solutions through the core. After a flow test was completed, the core was flushed with water for about 24 hours.…”
Section: Formation Damagementioning
confidence: 99%
See 2 more Smart Citations
“…The excess pressure drop may be due to the substantial extensional component present in this flow configuration (Khan et al, 2003;Durst et al, 1987;Jones and Walters, 1989;Saasen et al, 1990;Navarrete et al, 2000). Naverrete and Mitchell (1995) suggested that for the XG solutions, the flow was dominated by the shear viscosity, whereas for the PHPA solutions the flow was dominated by the extensional viscosity.…”
Section: Introductionmentioning
confidence: 92%